Mamburao a new eggplant (Solanum melongena L.) variety (2012)
An eggplant variety, “Mamburao” was developed by the Institute of Plant Breeding, Crop Science Cluster, College of Agriculture, University of the Philippines, Los Banos. This variety was evaluated under the National Cooperative Testing (NCT) in 2001-2003, and approved for release by the National Seed Industry Council (NSIC) of the Department of Agriculture. “Mamburao” is a selection from accession collected from Mamburac, Occidental Mindoro. An open-pollinated variety, the plant has erect and vigorous growth habit, spineless stems with medium anthocyanin coloration and hairiness. The flowers are light purple and the fruits are of the dark-purple type. The fruits can be harvested within 68-74 days after transplanting for dry and wet season, respectively. The marketable yield ranged from 13.35 t ha1 during dry season to 16.61 t h1 during wet season, outyielding the commercial check varieties. This variety was also observed to be resistant to bacterial wilt. The registry number of Mamburao is NSIC 2007 Eg 02.